Fabrication and characterization of single and bimetallic non-alloyed nanoparticles - Zakaria, Rozalina; Tan, Chee Long (Malaysian NANO-An International Journal, 2022)
We have demonstrated the fabrication of single and bimetallic Au and Ag nanoparticles on SiO2 substrate for light trapping application. Those nanoparticles were obtained by depositing 6nm and 8nm Au while 8nm and 10nm of Ag on SiO2 substrate. Then, the dewetting process takes place at 600oC for Au and 500oC for Ag. The particle distribution is quite non-uniform, making the shifting effect unclear and different from the previous result. However, the absorption effect of the BNNPs can be observed in this work, where it shows significantly broader peak spectra compared to both single Au and Ag NPs. This makes the BNNPs is the best candidate for selective detection sensors.